How to study television - Selby, Keith; Cowdery, Ron. (London : Macmillan, 1995)
This book is about: Studying television; Analysing a media text; Looking at aspects of a media text; ...
Keywords: Television criticism; Television plays; Television criticism; Television -- Semiotics; Television programs -- Plots, themes, etc; Television scripts -- Editing; Television plays